Synergy in the Transformative Formation of Women Religious: A Case of Hekima University College - Opondo, Jacinta Auma (Hekima Review, 2024)
Formation is foundational to religious life. It allows candidates to discover, acquire, assimilate and deepen their religious identity. Since family and societal culture constantly change, high-quality ongoing formative programs are indispensable. Yet, despite the aim of formation and the Church’s guidelines on holistic and transformative formation, formation challenges appear perennial and seem to call fora collaborative approach. This article highlights some challenges to the holistic and transformative formation, indicating magisterial responses. It also elucidates the Church’s invitation for a collaborative approach and buttresses the synergetic approach of Hekima University College (HUC)towards the transformative formation of African women religious.
paid
Keywords: Canon Law; Hekima Review; Religious life; Women Religious